Numerical Study of Fluid Dynamic and Heat Transfer in a Compact Heat Exchanger Using Nanofluids. (4th April 2012) - Gunnasegaran, P.; Shuaib, N. H.; Abdul Jalal, M. F.; Sandhita, E.
Abstract : Compact heat exchangers (CHEs) are characterized by a high surface area per unit volume, which can result in a higher efficiency than conventional heat exchangers. They are widely used in various applications in thermal fluid systems including automotive thermal fluid systems such as radiators for engine cooling systems. Recent development of nanotechnology brings out a new heat transfer coolant called "nanofluids, " which exhibit larger thermal properties than conventional coolants due to the presence of suspended nanosized composite particles in a base fluid. In this study, a numerical investigation using different types of nanoparticles in ethylene glycol-base fluid namely copper (Cu), diamond (DM), and silicon dioxide (SiO2 ) on automobile flat tube plate-fin cross-flow CHE is explored. The nanoparticles volume fraction of 2% is considered for all types of nanofluids examined in this study. The three-dimensional (3D) governing equations for both liquid flow and heat transfer are solved using a standard finite volume method (FVM) for the range of Reynolds number between 4000 and 7000. The standard κ -ε turbulence model with wall function is employed. The computational model is used to study the variations of shear stress, skin friction, and convective heat transfer coefficient. All parameters are found to yield higher magnitudes in the developing and developed regions along the flat tubes with the nanofluid flow than base fluid. The pressure drop is slightly larger for nanofluids but insignificant at outlet region of the tube. Hence, the usage of nanofluids in CHEs transfers more energy in a cost-effective manner than using conventional coolants.